Reflections on co-producing an obesity-prevention toolkit for Islamic Religious Settings: a qualitative process evaluation - Jennifer Hall; Rukhsana Rashid; Abida Rafiq; Kiran Fatima; Sally E. Barber; Sufyan Abid Dogra (BMC, 2024)
Abstract Background Islamic leaders, staff, and Muslim parents in the UK are supportive of healthy lifestyle intervention delivery through Islamic Religious Settings. Such interventions are necessary given high obesity rates in British South Asian (40%) compared to White British (32%) children of equivalent age. Co-production can facilitate the development of culturally appropriate health interventions, however it can be theoretically and practically challenging, and evaluation of co-production within an Islamic Religious Setting context is lacking. The aim of this study was to examine the feasibility and acceptability of taking a co-production approach to develop an obesity-prevention toolkit for Islamic Religious Settings. Methods An obesity-prevention toolkit for use in Islamic Religious Settings, incorporating physical activity, healthy diet, and organisational change, has been co-produced to be evidence-informed and contextually relevant. A qualitative process evaluation was employed to examine experiences of co-production. Semi-structured interviews (n = 15) and a focus group (n = 5) were conducted with toolkit co-production stakeholders, e.g., subject experts, an Islamic scholar, and Islamic Religious Setting staff. Transcripts were analysed inductively using reflexive thematic analysis. Results The analysis revealed four major themes regarding stakeholders' experiences of co-producing a childhood obesity-prevention toolkit for Islamic Religious Settings. These themes are: (1) attitudes towards obesity-prevention through Islamic Religious Settings, (2) benefits of co-production including capacity building and ownership (3) negotiating involvement, power, and perspectives within the co-production process, and (4) the complexities of effective communication in co-production. Conclusion This study adds to the evidence-base in support of delivering health promotion through faith settings. Taking a co-production approach to develop an obesity-prevention toolkit for Islamic Religious Settings provided benefit to the toolkit product and local stakeholders. The toolkit is currently being implemented across Bradford, UK and there is potential to adapt the toolkit to other geographical contexts, and for evaluating effectiveness for preventing obesity in British Muslim families.